Review about graphene- based biosensors for detection of SARS-COV-2 - Mena-Lizano, Daniel (2021)
Due to the health emergency produced by SARS-CoV-2, which has generated a pandemic, this work proposes a review on developed methods for the detection of Covid-19 based on graphene biosensors, considering their physicochemical properties. This research includes a compilation and analysis of information on this type of biosensors published in high-impact journals in recent years. For the development of the study, parameters such as detection time, detection limit, type of sensor, proteins that the biosensor detects, type of graphene, and cost were chosen to verify its effectiveness. The analyzed results demonstrate that most biosensors functionalizing the antibody of S, N protein or recombination of both, and some biosensors allow the detection of up to 4 types of proteins (C-reactive protein, IgG, IgM, and nucleapside). Several of the analyzed studies show a specific sequence detection of the virus and a low limit of detection (LOD) ranging from 0.1 fg/mL to 1 fg/mL, which allows detecting SARS-CoV-2 at low concentrations. In conclusion, the analysis indicates a feasible option for the implementation of graphene-based biosensors as an alternative to traditional test.